Social Media Fatigue : Causes and effects on 18 to 29 years old Finnish social users - Eerikäinen, Rosa (My University, 2023)
The purpose of this Master´s thesis was to examine what causes young adults from Finland to take a break from their social media usage. In addition, it aimed to find out why social networking sites create so many well-being issues for their users, especially young adults. What are the symptoms of social media fatigue? And lastly, the aim was to find out how young adults replace the time they have spent on social media when they take a break from it. The methods used for this research were quantitative and qualitative, and the purpose was to have young adults share their experiences and thoughts on social media fatigue, which is caused by the overuse of social media. Data was first gathered by using an online voluntary social media fatigue-themed survey with 14 questions in it to which 30 participants from Finland within the age range of 18 to 29-year-old responded within the period of one month. In addition, an analysis of a Finnish TV show Pause was conducted for this thesis to gather information on how the challenge of taking a two-week social media break would affect six Finnish social media influencers. The results were then compared to each other to find out if there would be any similarities between the results of the online survey and Pause. To support both findings, additional research was done. The results of the online survey showed that Finnish young adults have taken breaks from their social media usage due to either having trouble with concentration, sleeping, feeling too much pressure to be online since their friends are there, or struggling with self-esteem due to comparing themselves to other users or fighting unrealistic body image standards. In addition, the analysis of the TV show Pause showed, that because the six participants were challenged to take a two-week-long break from social media, most of them managed to stay offline the whole time. However, during their break, all six missed the connections they´ve built online and the social interactions they experience on social media daily. When comparing the results of the online survey and the analysis of Pause, the following similarities and differences were found. Both, the six social media influencers and the participants of the social media survey identified with 1) the idea that too much social media can interrupt sleep and thinking process, 2) they easily compare themselves to others while being online and 3) they wish to inhabit the methods of being more in control of their social media usage into their future social media using habits. In addition, Pause showed that influencers can experience social media as a positive place to be compared to non-influencers since it is their work platform, and they use it to communicate with their follower community that they have grown over time. Finally, it became clear that social media plays an active role in communication when it comes to today´s young adults and therefore it is difficult for them to stay offline. Therefore, for them to have more positive experiences while using social media in the future, the youth should be educated on how they can control their social media usage so that it does not cause them to suffer from so many of its negative effects causing social media fatigue.